تأثير جسيمات الفضة النانومترية على إنبات و نمو حبوب صنفين من القمح Triticum aestivum L. - باحويرث، محروس عبد الله بامسعود، سالم فرج (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN Experiments were performed in order to study the effect of immersing process on wheat Grains using uniform starch-stabilized silver nanoparticles (SNps). SNps, (M1,M2, and M3), were synthesized using silver nitrate (0.0005, 0.001and 0.002 M). The effect of SNps on seed germination, hypocotyls and semi root lengths of two Cultivars of wheat Grains Triticum aestivum L (Hadhramout3 and Kalisona ), was investigated. The wheat Grains were immersed for 20 minutes into the prepared SNps, along with distilled water as a control (M0). The Grains allowed to grow in petri dishes and measurements were taken after two weeks. For aqueous SNps prepped by 0.001M, the results show a remarkable effect on seeding speed, root length, dry and wet root weight. SNs prepared from 0.0005M show an observed a significant effect on length plumule and its wet weight. Significantly Hadhramout 3 shows better results in seeding speed, rootletlet length and plumule length, while Kalisona shows better results in wet and dry weight for rootletlet and and plumule root. Significant differences were notified in the two types and the concentration of the solutions.